Assessing China’s food security functional zoning for the water-energy-food-ecology system - Wei, Kunxiang; Zhang, Fan; Nie, Yingli; Lou, Chunjing; Guan, Xin (Frontiers in Sustainable Food Systems, 2025)
The food system faces severe global climate change and resource constraints, requiring consideration of its resource consumption and ecosystem impact. How to achieve food security under the water-energy-food-ecology (WEFE) system framework is a common challenge for all countries worldwide. Therefore, food security research from the perspective of WEFE holds great practical value and significance. It aligns with the vision of meeting people’s ecological resource needs and supports the UN Sustainable Development Goals. This study constructed a measurement system consisting of 4 subsystems and 17 indicators and used 2014–2021 panel data from 31 provincial-level regions to assess food security capability from the perspective of WEFE. The findings are as follows: (1) The food security guarantee capacity of 31 provincial-level regions improved from 2014 to 2021. (2) From 2014 to 2021, a small number of indicators contributed more significantly to food security capacity: agricultural fertilizer application, diesel use and pesticide use had an average annual contribution of 46.71% (potentially unsustainable with environmental risks). Additionally, some indicators saw a marked rise in contribution–over 8 years, water-saving irrigation area, cumulative soil erosion control area and green coverage area increased by 27.17, 22.29, and 25.93%, highlighting the key role of ecological environment and resource elements in the food system. (3) From 2014 to 2021, the relative importance (or influence) of the indicators on food security capacity remained relatively stable: pesticide use dropped significantly by 22.17%, while other indicators changed by less than 10%. (4) Based on the food security capacity assessment results, this study designed a functional zoning (seven types). The determination of functional zoning was based on the assessment results of the water, energy, food, and land subsystems within the food security capacity assessment results. Furthermore, it proposed targeted response strategies and policy recommendations to enhance the region’s food security, based on the characteristics of different functional areas. This study provided more reasonable functional zoning methods and more realistic results, which can promote balanced WEFE development, stabilize regional food supply, optimize water and energy use in production, protect ecology, strengthen global food security, and offer a Chinese solution for a new international food security paradigm.